'Mein lieber lúiß': Aloys von Harrach and the Diplomacies of Motherhood during the Last Years of Carlos II's Reign (1698–1701)1. (3rd July 2018) - Olivan-Santaliestra, Laura
Abstract : Aloys Thomas Raimund von Harrach (1669–1742) arrived as the imperial ambassador in Madrid in 1698 with the purpose of persuading Carlos II to designate Emperor Leopold I's second son, Archduke Charles of Austria, as heir to the Spanish Crown. Young and not very experienced for such a complicated embassy, Aloys relied on the inestimable help of his mother, Johanna Theresia von Lamberg, countess of Harrach (1639–1716). Having served with her husband, Ferdinand Bonaventura I von Harrach, who was ambassador from 1673 to 1677, Johanna possessed extensive knowledge of the Madrid court and connections. Based on more than eighty letters Johanna wrote to Aloys during his two-year embassy, this article discusses what I refer to as the diplomacies of motherhood. This never-examined correspondence reveals the influence of a powerful noblewoman at a critical moment in Carlos II's court, which was dominated by the unresolved question of the succession.